"Why do we do this?" : Moral Stress and the Affective Experience of Ethics in Practice - Rattay, Sonja; Vakkuri, Ville; Rozendaal, Marco C.; Shklovski, Irina (ACM, 2025)
A plethora of toolkits, checklists, and workshops have been developed to bridge the well-documented gap between AI ethics principles and practice. Yet little is known about effects of such interventions on practitioners. We conducted an ethnographic investigation in a major European city organization that developed and works to integrate an ethics toolkit into city operations. We find that the integration of ethics tools by technical teams destabilises their boundaries, roles, and mandates around responsibilities and decisions. This lead to emotional discomfort and feelings of vulnerability, which neither toolkit designers nor the organization had accounted for. We leverage the concept of moral stress to argue that this affective experience is a core challenge to the successful integration of ethics tools in technical practice. Even in this best case scenario, organisational structures were not able to deal with moral stress that resulted from attempts to implement responsible technology development practices.
Keywords: Moral stress; ethics in practice; responsible technology development; affective experience; fi=Viestintätieteet|en=Communication Studies|